Testing Signalling Theory: The Mediating Role of Profitability in the Relationship between Liquidity, Solvency, and Stock Prices - Intan Purbasari; Enok Nurhayati (Jurnal Ilmu Manajemen dan Ekonomika, 2026)
This study is motivated by the inconsistent findings of previous research regarding the effects of liquidity and solvency on stock prices, as well as the need to re-examine these relationships from the perspective of Signaling Theory. The study aims to analyze the effects of liquidity and solvency on stock prices and to examine the role of profitability as a mediating variable in building construction sub-sector companies listed on the Indonesia Stock Exchange (IDX). A quantitative research approach was employed using secondary data obtained from the annual financial statements and stock summaries of 12 building construction companies listed on the IDX during the 2019–2025 period. The study applied a saturated sampling technique, resulting in 84 firm-year observations. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 3 software. The results indicate that liquidity has no significant effect on stock prices, whereas solvency and profitability have positive and significant effects on stock prices. In addition, liquidity has a positive and significant effect on profitability, while solvency does not significantly affect profitability. The mediation analysis reveals that profitability significantly mediates the relationship between liquidity and stock prices but does not mediate the relationship between solvency and stock prices. These findings suggest that profitability serves as an important mechanism through which liquidity contributes to stock price enhancement, whereas the effect of solvency on stock prices occurs directly without being transmitted through profitability. This study contributes to the development of Signaling Theory by providing empirical evidence on the role of profitability in explaining the relationship between financial performance and stock prices. Furthermore, the study enriches the literature on the determinants of stock prices in Indonesia's building construction industry.